Restriction of Information about Socialist Countries in the Materials of I-III InternationalCorrespondents’ Meetings (1969-1971) in Poland - Piasecka, Renata (Respectus Philologicus, 2005)
After World War II, one of the more important areas of strict rationing in Poland was the issues connected with the situation within the block of socialist countries and economic integration under the RWPG (Council for Mutual Economic Assistance). The phenomenon discussed was characteristic of all socialist countries acquiring international reach. In Poland, the gradual removal of limitations on press information took place as late as the time between the “Prague Spring” and December events in 1970. A considerable contribution to that was the three first meetings of international correspondents accredited to socialist countries arranged by the Press Office of the Central Committee of the Polish United Workers’ Party in 1967-1971. Despite popular expectations and declarations made by the authorities, the directives prepared there did not significantly improve the contents of news bulletins delivered by Polish media.